Cognitive and Behavioral Changes Arising From Spirituality - Penman, Joy (Journal of religion and health, 2021)
This article aims to explore the concept of spiritual transformation and address the question, ‘How does spirituality bring about changes in cognition and behavior?’ It draws on the findings of a larger qualitative study that explored the essence of spirituality and spiritual engagement from the perspective of palliative care clients and caregivers. Four clients and ten caregivers from across regional South Australia participated in the larger study utilizing van Manen’s phenomenology. Secondary analysis of the qualitative data was undertaken to highlight the statements and phrases that portrayed the marked changes in thinking and behavior catalyzed by spirituality. The findings relate to the participants’ spiritual beliefs and practices that helped them journey through the process of death and dying. Spirituality is a plausible explanation of the transformation that occurred, manifested by new thinking and behavior.